2004
DOI: 10.1097/01.psy.0000143639.61693.ef
|View full text |Cite
|
Sign up to set email alerts
|

Acute Threat to the Social Self: Shame, Social Self-esteem, and Cortisol Activity

Abstract: Threat to the social self is an important elicitor of shame experience, decreases in social self-esteem and cortisol increases under demanding performance conditions. Cortisol changes may be specifically tied to the experience of emotions and cognitions reflecting low self-worth in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
336
8
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 424 publications
(378 citation statements)
references
References 40 publications
28
336
8
6
Order By: Relevance
“…It is unlikely that these mood reports reflected demand characteristics, as women who were primed to feel shame uniquely demonstrated a rise of cortisol levels following the mood priming. The unique effect of shame on cortisol reactivity is consistent with reports indicating that emotional responses to threats that undermine the social self are associated with HPA activation (Dickerson, Gruenewald, & Kemeny, 2004;Gruenewald, Kemeny, Aziz, & Fahey, 2004).…”
Section: Discussionsupporting
confidence: 74%
“…It is unlikely that these mood reports reflected demand characteristics, as women who were primed to feel shame uniquely demonstrated a rise of cortisol levels following the mood priming. The unique effect of shame on cortisol reactivity is consistent with reports indicating that emotional responses to threats that undermine the social self are associated with HPA activation (Dickerson, Gruenewald, & Kemeny, 2004;Gruenewald, Kemeny, Aziz, & Fahey, 2004).…”
Section: Discussionsupporting
confidence: 74%
“…The shame-causes-devaluation link seems unlikely. The experimental manipulation of criticism and publicity reliably boosts shame (23,38,62,63). In contrast, displays of shame or embarrassment attenuate an audience's devaluing response when the audience and the offender share common knowledge about the discrediting act (35,64,65).…”
Section: Discussionmentioning
confidence: 99%
“…Shame motivates one to avoid behaviors that could cause devaluation and to conceal damaging information (31). When damaging information is discovered, the shamed individual withdraws (32), accepts subordination (33,34), shows appeasement behavior (35), increases cooperativeness (36,37), and upregulates cortisol (38) as well as proinflammatory cytokines to defend against infection (39). This is accompanied by a stereotyped nonverbal display (22,40,41).…”
Section: Significancementioning
confidence: 99%
“…Even without an audience, preparing and giving a speech could be a very difficult task, which might cause at least some psychological stress (Gruenewald et al, 2004), so it is quite likely that it would cause physiological responses different from a rest (no-speech) condition. However, the previous studies did not compare the speech condition without an audience to a rest condition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they found that the actual physical presence of evaluative others produced greater cortisol responses than the presence of a video camera. Gruenewald, Kemeny, Aziz, and Fahey (2004) tested a hypothesis suggested by the Dickerson and Kemeny (2004) meta-analysis: namely, that the HPA system will be activated by threat to the social self. They conducted speech and mental arithmetic stress tasks with social evaluation present or absent.…”
Section: Introductionmentioning
confidence: 99%